A denitration catalyst, a denitration catalyst substrate, and a method for producing the same

CN122955503APending Publication Date: 2026-10-23PETROCHINA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510491184.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

该无机纤维板为硅铝酸盐纤维板、石英纤维板或硼纤维板,基材未做处理或改进,存在催化剂比表面积低、活性物质容易脱落的问题,影响催化剂的整体性能

Benefits of technology

[0030]本发明脱硝催化剂基体包括催化剂载体和涂覆助剂,分别引入结构调变剂氮化碳。由于经过不同次数的热处理中,类氮化碳通过聚合反应会形成尺寸不同的氮化碳,其中较大尺寸的氮化碳(粒径≥10nm)为二维片层结构,其与纳米TiO2、氧化钼或氧化钨、多孔SiO2通过化学键作用形成催化剂载体,提高了载体的电子传导能力,提高了脱硝反应性能;较小尺寸的氮化碳形成小介孔(直径为10nm以下)和微孔。由此,催化剂基体中形成了多级孔结构,丰富了催化剂的孔道结构,提高了催化剂基体的比表面积,进而提高了脱硝催化剂的比表面积,有利于反应物在催化剂内外表面上的扩散,促进反应物在催化剂上的吸附及解吸过程,加强了各物质间的传质能力,进而促使催化剂的活性更进一步提升。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides a denitration catalyst, a denitration catalyst substrate and a preparation method thereof. The denitration catalyst substrate comprises a fiber base material, a catalyst carrier and a coating aid, the catalyst carrier and the coating aid are loaded on the surface of the fiber base material, the catalyst carrier comprises carbon nitride, the particle size of the carbon nitride in the catalyst carrier is greater than or equal to 10 nm, and the coating aid comprises carbon nitride, the particle size of the carbon nitride in the coating aid is less than 10 nm. In the catalyst substrate of the application, a multi-stage pore structure is formed, the pore structure of the catalyst is enriched, the specific surface area of the catalyst substrate is improved, and the specific surface area of the denitration catalyst is further improved. The diffusion of reactants on the inner and outer surfaces of the catalyst is facilitated, the adsorption and desorption processes of the reactants on the catalyst are promoted, the mass transfer capacity among substances is strengthened, and the activity of the catalyst is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nitrogen oxide treatment technology, specifically to a denitrification catalyst, a denitrification catalyst matrix, and a preparation method thereof. Background Technology

[0002] Selective catalytic reduction (SCR) is the preferred technology for treating stationary source nitrogen oxides (NOx) due to its advantages such as high denitrification efficiency and no secondary pollution. Its core component is the denitrification catalyst. Based on the denitrification reaction temperature, denitrification catalysts can be divided into high-temperature catalysts (300–420℃) and medium-low temperature catalysts (below 300℃). Currently, refining and chemical enterprises have a large number of heating furnaces and heat exchange equipment, whose flue gas emission temperatures are typically below 300℃, placing higher demands on the medium-low temperature activity of denitrification catalysts.

[0003] In addition, based on the processing and molding method, denitrification catalysts can be divided into honeycomb, corrugated, and plate types. Among them, corrugated denitrification catalysts occupy a portion of the market share due to their advantages such as light weight, large geometric specific surface area, and short production cycle.

[0004] Corrugated denitrification catalysts are typically prepared by impregnating an active material onto a substrate, followed by drying and calcination. Commercially available corrugated denitrification catalysts primarily use glass fiber as the substrate, resulting in a small specific surface area of ​​the catalyst support. During use, flue gas erosion leads to a decline in the catalyst's denitrification performance, severely impacting the stable and compliant operation of the equipment.

[0005] Patent CN201810166192.1 discloses a substrate suitable for use in corrugated denitrification catalysts and its molding preparation method. The substrate contains, by mass percentage: 53%–56% SiO2, 27%–30% CaO, 12%–15% Al2O3, and 1%–3% MgO. The specific steps include: 1) preparing a molding liquid, which, by mass ratio, contains 6%–10% silane, 40%–60% methanol, and 30%–50% water; 2) setting the temperatures of the molding machine's drying oven and molding rollers, and feeding the material after the temperatures reach the set values; the set temperatures are: 290–300°C for the first stage of the drying oven, 280–290°C for the second stage, 500°C for the upper molding roller, and 230°C for the lower molding roller; 3) immersing the glass fiber mat in the molding liquid until it is completely saturated, then drying it in the drying oven before feeding it into the molding pressure rollers, and heating it at 230°C to form a corrugated shape; 4) cutting the corrugated plate into a custom-sized length using a cutting machine; the dimensions of the corrugated plate are: wave height 9.0 mm and wavelength 16.0 mm. This invention, by adjusting the corrugated molding control technology, prepares a substrate that conforms to a corrugated catalyst. Although the substrate meets the requirements for preparing corrugated catalysts, the active material is still prone to detachment during practical applications, and its erosion resistance needs to be further improved.

[0006] Patent CN201110321163.6 discloses a corrugated plate SCR denitrification catalyst. This invention uses stainless steel plates, stainless steel mesh, titanium plates, or titanium mesh as substrates, and employs electroplating, coating, or pressing methods to attach the carrier and active components. First, the catalyst carrier (titanium dioxide) is attached to the treated corrugated framework, and then the active components are attached on top. The catalyst substrate prepared by this process is lightweight, has a large specific surface area, and is less prone to dust accumulation. There is still significant room for improvement in the specific surface area of ​​the catalyst carrier and the adhesion strength to the substrate.

[0007] Patent CN201611002886.9 discloses a preparation process for a corrugated plate type denitration catalyst. This process uses an inorganic fiber board as the substrate. An active sol prepared from vanadium pentoxide, molybdenum trioxide, tungsten trioxide, titanium dioxide, and other substances is uniformly sprayed onto the upper and lower surfaces of the inorganic fiber board. The board is then rolled into a corrugated shape to obtain the finished catalyst. The catalyst prepared using this substrate and process has the advantages of low cost, short preparation time, high activity, and high wear resistance. However, the inorganic fiber board is made of aluminosilicate fiber, quartz fiber, or boron fiber. Since the substrate is not treated or improved, it suffers from low catalyst specific surface area and easy shedding of active materials, affecting the overall performance of the catalyst.

[0008] Therefore, further research is needed in this field on catalysts for medium- and low-temperature corrugated denitration. Summary of the Invention

[0009] The main objective of this invention is to provide a denitrification catalyst, a denitrification catalyst matrix, and a method for preparing the same. The problem to be solved is to increase the specific surface area of ​​the corrugated denitrification catalyst matrix, promote more uniform dispersion of active materials, improve the medium- and low-temperature denitrification performance of the catalyst, and at the same time, improve the catalyst's resistance to erosion and wear, and extend the catalyst's service life.

[0010] To achieve the above objectives, the present invention provides a denitrification catalyst matrix, comprising a fiber substrate, a catalyst support, and a coating aid, wherein the catalyst support and the coating aid are loaded on the surface of the fiber substrate, the catalyst support comprises carbon nitride, wherein the particle size of the carbon nitride in the catalyst support is greater than or equal to 10 nm, and the coating aid comprises carbon nitride, wherein the particle size of the carbon nitride in the coating aid is less than 10 nm.

[0011] In one embodiment of the denitrification catalyst matrix of the present invention, the catalyst support further includes nano-TiO2, molybdenum oxide and / or tungsten oxide, nano-SiO2, and glass fiber. Based on the total mass of the catalyst support as 100%, the nano-TiO2 accounts for 55-90%, carbon nitride accounts for 5-25%, the molybdenum oxide and / or tungsten oxide accounts for 2-15%, the nano-SiO2 accounts for 1-10%, and the glass fiber accounts for 1-5%.

[0012] In one embodiment of the denitrification catalyst matrix of the present invention, the carbon nitride in the catalyst support has a two-dimensional sheet structure and is chemically bonded to nano-TiO2, molybdenum oxide and / or tungsten oxide, and nano-SiO2; the carbon nitride in the coating additive forms mesopores and micropores with a diameter of less than 10 nm in the denitrification catalyst matrix.

[0013] In one embodiment of the denitrification catalyst matrix of the present invention, the carbon nitride is formed by high-temperature heat treatment of a carbon nitride-like material, wherein the carbon nitride-like material is one or a combination of several of urea, melamine, carbazide, and cyanamide; and the specific surface area of ​​the nano-TiO2 is 120–160 m². 2 / g; the diameter of the glass fiber is 15-25μm.

[0014] In one embodiment of the denitrification catalyst matrix of the present invention, the fiber substrate is a glass fiber substrate; the coating aids further include tetrabutyl titanate, tetraethyl orthosilicate, silica sol, polyethylene oxide and anhydrous ethanol.

[0015] In one embodiment of the denitrification catalyst matrix of the present invention, based on the total mass of the coating additives as 100%, the tetrabutyl titanate accounts for 15% to 50%, carbon nitride accounts for 1% to 15%, tetraethyl orthosilicate accounts for 10% to 35%, silica sol accounts for 5% to 25%, polyethylene oxide accounts for 1% to 8%, and anhydrous ethanol accounts for 10% to 35%.

[0016] To achieve the above objectives, the present invention also provides a method for preparing a denitrification catalyst matrix, comprising the following steps:

[0017] Step 1: Mix nano-TiO2, carbon nitride-like material, nano-SiO2, molybdenum source and / or tungsten source precursor, glass fiber and water to obtain a mixed suspension;

[0018] Step 2: Dry the mixed suspension obtained in Step 1, and then perform a first heat treatment under an inert atmosphere;

[0019] Step 3: Crush and sieve the material after the first heat treatment in Step 2 to obtain the catalyst support;

[0020] Step 4: The catalyst support and coating aid are used to form a coating slurry, which is then coated onto the fiber substrate, dried, and subjected to a second heat treatment to obtain the denitrification catalyst matrix.

[0021] The coating aid includes carbon nitride-like substances, and the carbon nitride-like substances in the coating aid may be the same as or different from the carbon nitride-like substances in step 1.

[0022] In one embodiment of the method for preparing the denitrification catalyst matrix of the present invention, step 1 involves mixing at a temperature of 80–100°C for 120–180 min, with stirring during the mixing process; and step 2 involves drying at a temperature of 100–140°C for 60–80 min.

[0023] In one embodiment of the method for preparing the denitrification catalyst matrix of the present invention, the first heat treatment is carried out at a temperature of 400-600°C for 2-4 hours; the second heat treatment is carried out under an inert atmosphere at a temperature of 500-600°C for 6-10 hours.

[0024] In one embodiment of the method for preparing the denitrification catalyst matrix of the present invention, the thickness of the fiber substrate is 0.5-1.2 mm; before the coating treatment, the fiber substrate is first punched with a pore diameter of 1-3 mm and a pore spacing of 50-150 mm.

[0025] In one embodiment of the denitrification catalyst matrix of the present invention, the molybdenum source precursor is one or a combination of several of ammonium tetramolybdate, ammonium heptamolybdate, and ammonium dodecamolybdate; and the tungsten source precursor is one or a combination of several of ammonium tungstate, ammonium metatungstate, and ammonium paratungstate.

[0026] In one embodiment of the denitrification catalyst matrix of the present invention, based on the total mass of the catalyst support as 100%, the nano-TiO2 accounts for 55-90%, carbon nitride accounts for 5-25%, the molybdenum oxide and / or tungsten oxide accounts for 2-15%, the nano-SiO2 accounts for 1-10%, and the glass fiber accounts for 1-5%.

[0027] In one embodiment of the denitrification catalyst matrix of the present invention, the coating aid further includes tetrabutyl titanate, tetraethyl orthosilicate, silica sol, polyethylene oxide, and anhydrous ethanol.

[0028] To achieve the above objectives, the present invention further provides a denitrification catalyst, comprising a denitrification catalyst matrix and an active component, wherein the active component is supported on the denitrification catalyst matrix, and the denitrification catalyst matrix is ​​the aforementioned denitrification catalyst matrix.

[0029] The beneficial effects of this invention are:

[0030] The denitrification catalyst matrix of this invention includes a catalyst support and a coating aid, with carbon nitride, a structure modifier, introduced in both. During different heat treatments, carbon nitride-like particles polymerize to form carbon nitrides of varying sizes. Larger carbon nitride particles (≥10 nm) have a two-dimensional lamellar structure, which chemically bonds with nano-TiO2, molybdenum oxide or tungsten oxide, and porous SiO2 to form the catalyst support, improving the electronic conductivity of the support and enhancing the denitrification reaction performance. Smaller carbon nitride particles form small mesopores (less than 10 nm in diameter) and micropores. Thus, a hierarchical porous structure is formed in the catalyst matrix, enriching the pore structure of the catalyst, increasing the specific surface area of ​​the catalyst matrix, and consequently increasing the specific surface area of ​​the denitrification catalyst. This facilitates the diffusion of reactants on the inner and outer surfaces of the catalyst, promotes the adsorption and desorption processes of reactants on the catalyst, strengthens the mass transfer between substances, and further enhances the activity of the catalyst. Detailed Implementation

[0031] The technical solution of the present invention will be described in detail below. The following embodiments are implemented under the premise of the technical solution of the present invention and a detailed implementation process is given. However, the protection scope of the present invention is not limited to the following embodiments. Structures or experimental methods that do not specify specific conditions in the following embodiments are generally performed under conventional conditions.

[0032] In this invention, unless otherwise specified, the terms "first," "second," and "third" do not indicate a sequence or limit the specific materials or steps; they are merely used to distinguish between materials that are not in the same step or within the same step. For example, "first" and "second" in "first heat treatment" and "second heat treatment" are simply used to indicate that they are not the same heat treatment.

[0033] The present invention provides a denitrification catalyst matrix, comprising a fiber substrate, a catalyst support, and a coating aid. The catalyst support and the coating aid are loaded on the surface of the fiber substrate. The catalyst support comprises carbon nitride, and the particle size of the carbon nitride in the catalyst support is greater than or equal to 10 nm. The coating aid comprises carbon nitride, and the particle size of the carbon nitride in the coating aid is less than 10 nm.

[0034] In this invention, the carbon nitride in the catalyst matrix has different particle sizes. Specifically, the carbon nitride in the catalyst support has a particle size greater than or equal to 10 nm, forming a two-dimensional sheet structure, and is chemically bonded to other components such as nano-TiO2, molybdenum oxide or tungsten oxide, and nano-SiO2. This improves the electronic conductivity of the support and enhances the denitrification reaction performance of the catalyst. The carbon nitride in the coating additive has a particle size less than 10 nm, mainly forming mesopores and micropores with a diameter of less than 10 nm in the catalyst matrix. This results in a catalyst matrix with a rich hierarchical pore structure and a high specific surface area, which facilitates the diffusion of reactants on the inner and outer surfaces of the catalyst, promotes the adsorption and desorption processes of reactants on the catalyst, strengthens the mass transfer between substances, and further enhances the activity of the catalyst.

[0035] In one embodiment, the coating aid of the present invention includes tetrabutyl titanate, carbon nitride, tetraethyl orthosilicate, silica sol, polyethylene oxide, and anhydrous ethanol. Carbon nitride, for example, has a particle size of less than 10 nm, which further enriches the pore structure of the catalyst matrix, increases the specific surface area of ​​the catalyst matrix, facilitates the diffusion of reactants on the inner and outer surfaces of the catalyst, and promotes the adsorption and desorption processes of reactants on the catalyst.

[0036] In one embodiment, the catalyst support of the present invention further includes nano-TiO2, molybdenum oxide and / or tungsten oxide, nano-SiO2, and glass fiber.

[0037] In this invention, a catalyst support and a coating aid are loaded onto the surface of a fiber substrate. For example, the catalyst support and the coating aid form a coating slurry that is coated onto the fiber substrate. The carbon nitride in the catalyst support and the carbon nitride in the coating aid are formed by the polymerization reaction of carbon nitride-like substances during heat treatment. In one embodiment, the carbon nitride-like substances are one or a combination of urea, melamine, carbazide, and cyanamide. In one embodiment, the carbon nitride in the catalyst support is obtained through two heat treatments, and the carbon nitride in the coating aid is obtained through one heat treatment.

[0038] In this invention, a coating slurry formed from a catalyst support and coating aids is applied to a fiber substrate, for example, to both sides of the fiber substrate. In one embodiment, water, such as deionized water, is added to the coating slurry during its formation; however, this invention is not particularly limited in its application.

[0039] Furthermore, the nano-SiO2 of the present invention is porous SiO2, which can further enrich the pore structure of the catalyst matrix and increase the specific surface area of ​​the catalyst matrix.

[0040] The present invention does not impose any particular limitation on the fiber substrate. In one embodiment, the fiber substrate is a glass fiber substrate with a thickness of 0.5-1.5 mm, preferably 0.5-1.2 mm.

[0041] In this invention, the catalyst support comprises nano-TiO2, carbon nitride, molybdenum oxide and / or tungsten oxide, nano-SiO2, and glass fiber. The glass fiber in the catalyst support has a diameter of, for example, 10-35 μm, preferably 15-25 μm.

[0042] This invention does not impose any particular limitation on nano-TiO2; any commercially available product can be used. In one embodiment, the specific surface area of ​​the nano-TiO2 is 120–160 m². 2 / g.

[0043] In one embodiment, based on the total mass of the catalyst support (100%), the catalyst support comprises 55-90% nano-TiO2, 5-25% carbon nitride, 2-15% molybdenum oxide and / or tungsten oxide, 1-10% nano-SiO2, and 1-5% glass fiber. Preferably, the composition is 65-80% nano-TiO2, 10-20% carbon nitride, 5-10% molybdenum oxide and / or tungsten oxide, 4-8% nano-SiO2, and 2-4% glass fiber.

[0044] In one embodiment, based on the total mass of the coating additives as 100%, tetrabutyl titanate accounts for 15% to 50%, carbon nitride accounts for 1% to 15%, tetraethyl orthosilicate accounts for 10% to 35%, silica sol accounts for 5% to 25%, polyethylene oxide accounts for 1% to 8%, and anhydrous ethanol accounts for 10% to 35%.

[0045] The present invention also provides a method for preparing the above-mentioned denitrification catalyst matrix, comprising the following steps:

[0046] Step 1: Mix nano-TiO2, carbon nitride-like substances, nano-SiO2, molybdenum or tungsten source precursors, glass fibers and water to obtain a mixed suspension;

[0047] Step 2: Dry the mixed suspension obtained in Step 1, and then perform a first heat treatment under an inert atmosphere;

[0048] Step 3: Crush and sieve the material after the first heat treatment in Step 2 to obtain the catalyst support;

[0049] Step 4: The catalyst support and coating aid are used to form a coating slurry, which is then coated onto the fiber substrate, dried, and subjected to a second heat treatment to obtain the denitrification catalyst matrix.

[0050] In this invention, carbon nitride-like particles are added during the preparation of the catalyst support, and the coating aid also includes carbon nitride-like particles. The carbon nitride-like particles in the catalyst support undergo two heat treatments, resulting in larger particle sizes after polymerization. The carbon nitride-like particles in the coating aid undergo one heat treatment, resulting in smaller particle sizes after polymerization. The larger carbon nitride particles can form a catalyst support through chemical bonding with other components in the catalyst support, improving the electronic conductivity of the support and enhancing the denitration reaction performance. The smaller carbon nitride particles form small mesopores and micropores. Thus, a hierarchical porous structure is formed in the catalyst matrix, enriching the pore structure of the catalyst, increasing the specific surface area of ​​the catalyst matrix, and consequently increasing the specific surface area of ​​the denitration catalyst. This facilitates the diffusion of reactants on the inner and outer surfaces of the catalyst, promotes the adsorption and desorption processes of reactants on the catalyst, strengthens the mass transfer between substances, and further enhances the activity of the catalyst.

[0051] Some of the substances used in the preparation process have been described in detail above, and will not be repeated here.

[0052] In one embodiment, the molybdenum source precursor is one or a combination of several of ammonium tetramolybdate, ammonium heptamolybdate, and ammonium dodecamolybdate; the tungsten source precursor is one or a combination of several of ammonium tungstate, ammonium metatungstate, and ammonium paratungstate.

[0053] In one embodiment, the water in step 1 is deionized water, and the amount of water used is 1 to 1.5 times the total mass of the other components (nano-TiO2, carbon nitride-like substances, nano-SiO2, molybdenum or tungsten source precursors, and glass fiber). The mixing process in step 1 can be carried out in a mixing kettle, which allows for more uniform mixing. In another embodiment, stirring is performed during the mixing process in step 1, the mixing temperature is 80 to 100°C, and the mixing time is 120 to 180 minutes.

[0054] In one embodiment, the drying temperature in step 2 is 100–140°C, and the drying time is 60–80 min. The first heat treatment in step 2 is carried out under an inert atmosphere, which can be nitrogen, argon, etc. In another embodiment, the inert atmosphere is a mixture of nitrogen and argon, wherein nitrogen accounts for 50–70 vol% and argon accounts for 30–50 vol%. The temperature of the first heat treatment is 400–600°C, and the time is 2–4 h. During the first heat treatment, carbon nitride-like substances undergo a polymerization reaction to obtain carbon nitride of different sizes.

[0055] The present invention does not specifically limit the crushing method in step 3, such as ball milling. Then, it is sieved, for example, with a mesh size of 40 to 80, to obtain the catalyst support.

[0056] Step 4 involves coating the catalyst support and coating aid into a coating slurry on a fiber substrate, drying it, and then performing a second heat treatment to obtain the denitrification catalyst matrix.

[0057] In one embodiment, the mass content of the catalyst support in the coating slurry is 35-45%, and the mass content of the coating additive is 55-65%.

[0058] In one embodiment, the coating aid further includes water, such as deionized water. Based on 100% of the total mass of the coating aid, the coating aid comprises: 15%–50% tetrabutyl titanate, 1–15% carbon nitride-like material, 10%–35% tetraethyl orthosilicate, 5%–25% silica sol, 1–8% polyethylene oxide, 10%–35% anhydrous ethanol, and 5%–20% water. Preferably, the composition is 20%–40% tetrabutyl titanate, 5–10% carbon nitride-like material, 15%–30% tetraethyl orthosilicate, 10%–20% silica sol, 2–5% polyethylene oxide, 15%–25% anhydrous ethanol, and 10%–15% deionized water.

[0059] In this invention, the carbon nitride-like substances added to the catalyst support and the carbon nitride-like substances added to the coating aid may be the same or different.

[0060] In one embodiment, the fiber substrate is punched before coating, with a hole diameter of 1-3 mm and a hole spacing of 50-150 mm. After punching, the slurry on the front and back of the fiber substrate is interlocked through the mesh holes. Under the action of chemical bonds, the bonding force between the coating slurry and the fiber substrate is greatly improved, enhancing the firmness of the coating slurry on the fiber substrate, ensuring the overall stability of the coating, and thus enhancing the erosion resistance.

[0061] In one embodiment, step 4 involves drying at a temperature of 50–70°C for 80–150 minutes. The second heat treatment is carried out under an inert atmosphere at a temperature of 500–600°C for 6–10 hours; the inert atmosphere can be nitrogen, argon, etc. In another embodiment, the inert atmosphere is a mixture of nitrogen and argon, wherein nitrogen accounts for 60–80 vol% and argon accounts for 20–40 vol%.

[0062] After undergoing two high-temperature heat treatments, the denitrification catalyst matrix of this invention integrates the fiber substrate, catalyst support, and coating additives into a unified whole through the combined action of multiple chemical bonds, thereby enhancing the overall stability of the catalyst matrix. Simultaneously, the introduction of strength-enhancing glass fibers and silicon-based structural materials into the catalyst matrix improves its erosion resistance and wear resistance, extending the catalyst's service life.

[0063] The denitrification catalyst matrix described above in this invention can be used to prepare a denitrification catalyst. The denitrification catalyst includes a denitrification catalyst matrix and an active component. The active component is supported on the denitrification catalyst matrix, for example, by impregnation, followed by drying and calcination to obtain the denitrification catalyst.

[0064] The denitrification catalyst of this invention is suitable for denitrification of medium and low temperature flue gas. It is a corrugated denitrification catalyst with abundant catalyst channel structure, high specific surface area, uniform dispersion of active material on catalyst matrix, high erosion resistance and wear resistance, and long service life, which can ensure the stable operation of the device for a longer period of time.

[0065] The technical solution of the present invention will be described in detail below with reference to embodiments thereof. Obviously, the described embodiments are only a part of the implementation methods of the present invention, and not all of them.

[0066] The catalyst performance evaluation conditions of this invention are: space velocity 4500 h⁻¹ -1 The reaction temperature was 260℃, N2 was the equilibrium gas, and NOx was 200~300mg / Nm³. 3 , O2 1.0~2.0vol%, H2O 5~10vol%.

[0067] In the embodiments of the present invention, the catalyst matrix raw materials are all sourced from Sinopharm Chemical Reagent Co., Ltd.

[0068] In the embodiments of the present invention, the denitrification performance of the catalyst was measured using a denitrification evaluation device from Beijing Kunlun Yongtai Technology Co., Ltd.

[0069] In the embodiments of the present invention, the specific surface area of ​​the catalyst matrix was measured using a physical adsorption instrument from Micron Technology.

[0070] In the embodiments of the present invention, the catalyst substrate coating peeling rate was tested by setting up equipment and calculated based on the mass loss of the catalyst before and after rinsing. The formula is: peeling rate = (mass before rinsing - mass after rinsing) / mass before rinsing * 100%.

[0071] Example 1:

[0072] Nano-TiO2 (specific surface area 120m²) 2 The following components were mixed in a ratio of 72%:14%:5%:6%:3%:(1.3 times the total amount of raw materials): carbon nitride (50wt% urea, 50wt% carbazide), molybdenum source precursor (ammonium heptamolybdate), porous SiO2, glass fiber (20μm in diameter), and deionized water. The mixture was stirred uniformly for 160 min at 95℃ to obtain a mixed suspension. The mixed suspension was dried at 120℃ for 80 min and then heat-treated at 500℃ for 3 h in an inert gas atmosphere of 60% nitrogen and 40% argon. The heat-treated support powder was ball-milled and passed through a 40-mesh sieve to obtain the catalyst support.

[0073] A coating aid composed of 32% tetrabutyl titanate, 5% carbon nitride-like substance (urea), 18% tetraethyl orthosilicate, 15% silica sol, 3% polyethylene oxide, 14% anhydrous ethanol, and 13% deionized water was prepared with a catalyst support to form a coating slurry. This slurry was coated onto a glass fiber substrate with a thickness of 1.0 mm, a pore size of 2 mm, and a pore spacing of 120 mm. The substrate was dried at 60 °C for 100 min and then heat-treated at 580 °C for 6 h in a nitrogen atmosphere of 60% nitrogen and argon atmosphere to obtain a corrugated SCR catalyst matrix.

[0074] The prepared active material was impregnated onto an SCR catalyst matrix, then dried and calcined to obtain a high specific surface area corrugated denitration catalyst. The active material, vanadium pentoxide, accounted for 2.5% of the total mass of the catalyst support and coating additives. BET testing showed that the catalyst had a specific surface area of ​​85.5 m². 2 / g, the catalyst substrate coating peeling rate was 4.4%. The catalyst was evaluated under the test conditions, and its denitrification efficiency was 95.6%.

[0075] Comparative Example 1:

[0076] Nano-TiO2 (specific surface area 120m²) 2 The following components were mixed in a ratio of 72%:5%:6%:3%:(1.3 times the total amount of raw materials): molybdenum source precursor (ammonium heptamolybdate), porous SiO2, glass fiber (20 μm in diameter), and deionized water. The mixture was stirred uniformly for 160 min at 95 °C to obtain a mixed suspension. The mixed suspension was dried at 120 °C for 80 min and then heat-treated at 500 °C for 3 h in an inert gas atmosphere of 60% nitrogen and 40% argon. The heat-treated support powder was ball-milled and passed through a 40-mesh sieve to obtain the catalyst support.

[0077] A coating aid composed of 32% tetrabutyl titanate, 18% tetraethyl orthosilicate, 15% silica sol, 3% polyethylene oxide, 14% anhydrous ethanol, and 13% deionized water was prepared with a catalyst support to form a coating slurry. This slurry was then coated onto a glass fiber substrate with a thickness of 1.0 mm, a pore size of 2 mm, and a pore spacing of 120 mm. The substrate was dried at 60 °C for 100 min and then heat-treated at 580 °C for 6 h in a nitrogen atmosphere of 60% nitrogen and argon atmosphere to obtain a corrugated SCR catalyst matrix.

[0078] The prepared active material was impregnated onto an SCR catalyst matrix, then dried and calcined to obtain a high specific surface area corrugated denitration catalyst. The active material, vanadium pentoxide, accounted for 2.5% of the total mass of the catalyst support and coating additives. BET testing showed that the catalyst had a specific surface area of ​​75.8 m². 2 / g, the catalyst substrate coating peeling rate was 5.4%. The catalyst was evaluated under the test conditions, and its denitrification efficiency was 90.5%.

[0079] Example 2:

[0080] Nano-TiO2 (specific surface area 140m²) 2 / g), carbon nitride-like carbon (carbonyl hydrazine), tungsten source precursor (ammonium metatungstate), porous SiO2, glass fiber (15μm in diameter), and deionized water were added to a mixing kettle in the following proportions: 68%: 18%: 7%: 5%: 2%: (1.4 times the total amount of raw materials). The mixture was stirred uniformly for 160 min at 90℃ to obtain a mixed suspension. The mixed suspension was dried at 120℃ for 70 min and then heat-treated at 500℃ for 4 h in an inert gas atmosphere of 70% nitrogen and 43% argon. The heat-treated support powder was ball-milled and passed through an 80-mesh sieve to obtain the catalyst support.

[0081] A coating aid composed of 25% tetrabutyl titanate, 8% carbon nitride (carbon hydrazine), 24% tetraethyl orthosilicate, 10% silica sol, 3% polyethylene oxide, 20% anhydrous ethanol, and 10% deionized water was prepared with a catalyst support to form a coating slurry. This slurry was coated onto a glass fiber substrate with a thickness of 0.7 mm, a pore size of 1 mm, and a pore spacing of 100 mm. The substrate was dried at 70 °C for 100 min and then heat-treated at 550 °C for 6 h in a gas atmosphere of 70% nitrogen and 30% argon to obtain a corrugated SCR catalyst matrix.

[0082] The prepared active material was impregnated onto an SCR catalyst matrix, then dried and calcined to obtain a high specific surface area corrugated denitration catalyst. The active material, vanadium pentoxide, accounted for 2.5% of the total mass of the catalyst support and coating additives. BET testing showed that the catalyst had a specific surface area of ​​88.9 m². 2 / g. The catalyst substrate coating peeling rate was 5.1%. The catalyst was evaluated under the test conditions, and its denitrification efficiency was 97.6%.

[0083] Example 3:

[0084] Nano-TiO2 (specific surface area 140m²) 2The following components were added to a mixing vessel in the following proportions: 66% (g), carbon nitride-like substances (40% urea, 60% melamine), molybdenum source precursor (ammonium heptamolybdate), porous SiO2, glass fiber (20 μm in diameter), and deionized water. The mixture was stirred uniformly for 160 min at 95 °C to obtain a mixed suspension. The mixed suspension was dried at 120 °C for 80 min and then heat-treated at 480 °C for 4 h in an inert gas atmosphere of 60% nitrogen and 40% argon. The heat-treated carrier powder was then ball-milled and passed through an 80-mesh sieve to obtain the catalyst carrier.

[0085] A coating aid composed of 22% tetrabutyl titanate, 8% carbon nitride (carbon hydrazine), 20% tetraethyl orthosilicate, 16% silica sol, 2% polyethylene oxide, 19% anhydrous ethanol, and 13% deionized water was prepared with a catalyst support to form a coating slurry. This slurry was coated onto a glass fiber substrate with a thickness of 1.0 mm, a pore size of 3 mm, and a pore spacing of 150 mm. The substrate was dried at 70 °C for 120 min and then heat-treated at 500 °C for 8 h in a nitrogen atmosphere of 60% nitrogen and argon atmosphere to obtain a corrugated SCR catalyst matrix.

[0086] The prepared active material was impregnated onto an SCR catalyst matrix, then dried and calcined to obtain a high specific surface area corrugated denitration catalyst. The active material, vanadium pentoxide, accounted for 2.5% of the total mass of the catalyst support and coating additives. BET testing showed that the catalyst had a specific surface area of ​​89.4 m². 2 / g. The catalyst substrate coating peeling rate was 4.1%. The catalyst was evaluated under the test conditions, and its denitrification efficiency was 98.5%.

[0087] Comparative Example 2:

[0088] Nano-TiO2 (specific surface area 140m²) 2 The following components were added sequentially to a mixing vessel in the following proportions: 66% (g), molybdenum source precursor (ammonium heptamolybdate), porous SiO2, glass fiber (20 μm in diameter), and deionized water. The mixture was stirred uniformly for 160 min at 95 °C to obtain a mixed suspension. The mixed suspension was dried at 120 °C for 80 min and then heat-treated at 480 °C for 4 h in an inert gas atmosphere of 60% nitrogen and 40% argon. The heat-treated carrier powder was then ball-milled and passed through an 80-mesh sieve to obtain the catalyst carrier.

[0089] A coating aid composed of 22% tetrabutyl titanate, 20% tetraethyl orthosilicate, 16% silica sol, 2% polyethylene oxide, 19% anhydrous ethanol, and 13% deionized water was prepared with a catalyst support to form a coating slurry. This slurry was coated onto a glass fiber substrate with a thickness of 1.0 mm, a pore size of 3 mm, and a pore spacing of 150 mm. The substrate was dried at 70 °C for 120 min and then heat-treated at 500 °C for 8 h in a nitrogen atmosphere of 60% nitrogen and argon atmosphere to obtain a corrugated SCR catalyst matrix.

[0090] The prepared active material was impregnated onto an SCR catalyst matrix, then dried and calcined to obtain a high specific surface area corrugated denitration catalyst. The active material, vanadium pentoxide, accounted for 2.5% of the total mass of the catalyst support and coating additives. BET testing showed that the catalyst had a specific surface area of ​​78.9 m². 2 / g. The catalyst substrate coating peeling rate was 6.7%. The catalyst was evaluated under the test conditions, and its denitrification efficiency was 93.5%.

[0091] Example 4:

[0092] Nano-TiO2 (specific surface area 160m²) 2 The following components were added to a mixing vessel in the following proportions: 76% : 13% : 5% : 4% : 2% : (1.4 times the total amount of raw materials). The mixture was stirred uniformly for 170 min at 95 °C to obtain a mixed suspension. The mixed suspension was dried at 135 °C for 60 min and then heat-treated at 560 °C for 4 h in an inert gas atmosphere of 70% nitrogen and 30% argon. The heat-treated carrier powder was ball-milled and passed through an 80-mesh sieve to obtain the catalyst carrier.

[0093] A coating aid composed of 35% tetrabutyl titanate, 5% carbon nitride-like substance (urea), 18% tetraethyl orthosilicate, 12% silica sol, 5% polyethylene oxide, 15% anhydrous ethanol, and 10% deionized water was prepared with a catalyst support to form a coating slurry. The slurry was coated onto a glass fiber substrate with a thickness of 1.0 mm, a pore size of 2 mm, and a pore spacing of 120 mm. The substrate was dried at 70 °C for 140 min and then heat-treated at 560 °C for 10 h in a gas atmosphere of 70% nitrogen and 30% argon to obtain a corrugated SCR catalyst matrix.

[0094] The prepared active material was impregnated onto an SCR catalyst matrix, then dried and calcined to obtain a high specific surface area corrugated denitration catalyst. The active material, vanadium pentoxide, accounted for 2.5% of the total mass of the catalyst support and coating additives. BET testing showed that the catalyst had a specific surface area of ​​92.5 m². 2 / g. The catalyst substrate coating peeling rate was 4.7%. The catalyst was evaluated under the test conditions, and its denitrification efficiency was 99.5%.

[0095] Example 5:

[0096] Nano-TiO2 (specific surface area 160m²) 2 The following components were added to a mixing vessel in the following proportions: 1 / g of carbon nitride (urea), 20 μm of molybdenum precursor (ammonium tetramolybdate), porous SiO2, glass fiber (20 μm in diameter), and deionized water. The mixture was stirred uniformly for 180 min at 95 °C to obtain a mixed suspension. The mixed suspension was dried at 140 °C for 80 min and then heat-treated at 560 °C for 4 h in an inert gas atmosphere of 70% nitrogen and 30% argon. The heat-treated carrier powder was then ball-milled and passed through a 60-mesh sieve to obtain the catalyst carrier.

[0097] A coating aid composed of 35% tetrabutyl titanate, 5% carbon nitride-like substance (urea), 18% tetraethyl orthosilicate, 12% silica sol, 5% polyethylene oxide, 15% anhydrous ethanol, and 10% deionized water was prepared with a catalyst support to form a coating slurry. The slurry was coated onto a glass fiber substrate with a thickness of 1.0 mm, a pore size of 2 mm, and a pore spacing of 100 mm. The substrate was dried at 70 °C for 150 min and then heat-treated at 550 °C for 10 h in a gas atmosphere of 80% nitrogen and 20% argon to obtain a corrugated SCR catalyst matrix.

[0098] The prepared active material was impregnated onto an SCR catalyst matrix, then dried and calcined to obtain a high specific surface area corrugated denitration catalyst. The active material, vanadium pentoxide, accounted for 2.5% of the total mass of the catalyst support and coating additives. BET testing showed that the catalyst had a specific surface area of ​​92.7 m². 2 / g. The catalyst substrate coating peeling rate was 4.6%. The catalyst was evaluated under the test conditions, and its denitrification efficiency was 94.3%.

[0099] Comparative Example 3:

[0100] Nano-TiO2 (specific surface area 130m²) 2The following components were added sequentially to a mixing vessel in the following proportions: 71% (g), 15% (ammonium tetramolybdate), porous SiO2, glass fiber (25 μm in diameter), and deionized water. The mixture was stirred uniformly for 180 min at 90 °C to obtain a mixed suspension. The mixed suspension was dried at 120 °C for 100 min and then heat-treated at 550 °C for 2 h in an inert gas atmosphere of 70% nitrogen and 30% argon. The heat-treated carrier powder was then ball-milled and passed through a 60-mesh sieve to obtain the catalyst carrier.

[0101] A coating aid composed of 30% tetrabutyl titanate, 18% tetraethyl orthosilicate, 12% silica sol, 3% polyethylene oxide, 16% anhydrous ethanol, and 15% deionized water was prepared with a catalyst support to form a coating slurry. This slurry was coated onto a glass fiber substrate with a thickness of 1.2 mm, a pore size of 3 mm, and a pore spacing of 150 mm. The substrate was dried at 70 °C for 120 min and then heat-treated at 550 °C for 10 h in a gas atmosphere of 80% nitrogen and 20% argon to obtain a corrugated SCR catalyst matrix.

[0102] The prepared active material was impregnated onto an SCR catalyst matrix, then dried and calcined to obtain a high specific surface area corrugated denitration catalyst. The active material, vanadium pentoxide, accounted for 2.5% of the total mass of the catalyst support and coating additives. BET testing showed that the catalyst had a specific surface area of ​​76.9 m². 2 / g. The catalyst substrate coating peeling rate was 8.1%. The catalyst was evaluated under the test conditions, and its denitrification efficiency was 89.7%.

[0103] As shown in the examples and comparative examples, the denitrification catalyst matrix of the present invention has a high specific surface area, abundant pore structure, and uniform dispersion of active materials. The catalyst exhibits high denitrification activity and a high denitrification rate at medium and low temperatures. Simultaneously, the denitrification catalyst of the present invention possesses strong anti-erosion and anti-wear properties, thus extending the service life of the SCR catalyst. Comparing Examples 2 and 3, with the same specific surface area of ​​titanium dioxide, the denitrification performance of the catalyst increases when the carbon nitride content is increased. The present invention, by introducing the structure modifier carbon nitride during catalyst preparation, can increase the specific surface area of ​​the catalyst and construct a hierarchical porous structure with both micropores and mesopores. This is beneficial for improving the transport and adsorption of NOx and the reducing agent NH3 in the denitrification reaction, thereby enhancing the denitrification performance.

[0104] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the claims of the present invention.

Claims

1. A denitrification catalyst matrix, characterized in that, The device includes a fiber substrate, a catalyst support, and a coating aid. The catalyst support and the coating aid are loaded on the surface of the fiber substrate. The catalyst support includes carbon nitride, and the particle size of the carbon nitride in the catalyst support is greater than or equal to 10 nm. The coating aid includes carbon nitride, and the particle size of the carbon nitride in the coating aid is less than 10 nm.

2. The denitrification catalyst matrix according to claim 1, characterized in that, The catalyst support further includes nano-TiO2, molybdenum oxide and / or tungsten oxide, nano-SiO2, and glass fiber. Based on the total mass of the catalyst support as 100%, the nano-TiO2 accounts for 55-90%, carbon nitride accounts for 5-25%, the molybdenum oxide and / or tungsten oxide accounts for 2-15%, the nano-SiO2 accounts for 1-10%, and the glass fiber accounts for 1-5%.

3. The denitrification catalyst matrix according to claim 2, characterized in that, The carbon nitride in the catalyst support has a two-dimensional sheet structure and is chemically bonded to nano-TiO2, molybdenum oxide and / or tungsten oxide, and nano-SiO2; the carbon nitride in the coating additive forms mesopores and micropores with a diameter of less than 10 nm in the denitrification catalyst matrix.

4. The denitrification catalyst matrix according to claim 2, characterized in that, Carbon nitride is formed by high-temperature heat treatment of carbon nitride-like substances, wherein the carbon nitride-like substances are one or a combination of urea, melamine, carbazide, and cyanamide; the specific surface area of ​​the nano-TiO2 is 120–160 m² / g. 2 / g; the diameter of the glass fiber is 15-25μm.

5. The denitrification catalyst matrix according to claim 1, characterized in that, The fiber substrate is a glass fiber substrate; the coating additives also include tetrabutyl titanate, tetraethyl orthosilicate, silica sol, polyethylene oxide and anhydrous ethanol.

6. The denitrification catalyst matrix according to claim 5, characterized in that, Based on the total mass of the coating additives as 100%, the tetrabutyl titanate accounts for 15% to 50%, carbon nitride accounts for 1% to 15%, the tetraethyl orthosilicate accounts for 10% to 35%, the silica sol accounts for 5% to 25%, the polyethylene oxide accounts for 1% to 8%, and the anhydrous ethanol accounts for 10% to 35%.

7. A method for preparing a denitrification catalyst matrix, characterized in that, Includes the following steps: Step 1: Mix nano-TiO2, carbon nitride-like material, nano-SiO2, molybdenum source and / or tungsten source precursor, glass fiber and water to obtain a mixed suspension; Step 2: Dry the mixed suspension obtained in Step 1, and then perform a first heat treatment under an inert atmosphere; Step 3: Crush and sieve the material after the first heat treatment in Step 2 to obtain the catalyst support; Step 4: The catalyst support and coating aid are used to form a coating slurry, which is then coated onto the fiber substrate, dried, and subjected to a second heat treatment to obtain the denitrification catalyst matrix. The coating aid includes carbon nitride-like substances, and the carbon nitride-like substances in the coating aid may be the same as or different from the carbon nitride-like substances in step 1.

8. The method for preparing the denitrification catalyst matrix according to claim 7, characterized in that, Step 1: The mixing temperature is 80-100℃, the mixing time is 120-180 min, and stirring is carried out during the mixing process; Step 2: The drying temperature is 100-140℃, and the drying time is 60-80 min.

9. The method for preparing the denitrification catalyst matrix according to claim 7, characterized in that, The first heat treatment is carried out at a temperature of 400–600°C for 2–4 hours; the second heat treatment is carried out in an inert atmosphere at a temperature of 500–600°C for 6–10 hours.

10. The method for preparing the denitrification catalyst matrix according to claim 7, characterized in that, The thickness of the fiber substrate is 0.5 to 1.2 mm; before coating, the fiber substrate is punched with a hole diameter of 1 to 3 mm and a hole spacing of 50 to 150 mm.

11. The denitrification catalyst matrix according to claim 7, characterized in that, The molybdenum source precursor is one or a combination of several of ammonium tetramolybdate, ammonium heptamolybdate, and ammonium dodecamolybdate; the tungsten source precursor is one or a combination of several of ammonium tungstate, ammonium metatungstate, and ammonium paratungstate.

12. The denitrification catalyst matrix according to claim 7, characterized in that, Based on the total mass of the catalyst support as 100%, the nano-TiO2 accounts for 55-90%, carbon nitride accounts for 5-25%, molybdenum oxide and / or tungsten oxide accounts for 2-15%, nano-SiO2 accounts for 1-10%, and glass fiber accounts for 1-5%.

13. The denitrification catalyst matrix according to claim 7, characterized in that, The coating aids also include tetrabutyl titanate, tetraethyl orthosilicate, silica sol, polyethylene oxide, and anhydrous ethanol.

14. A denitration catalyst, comprising a denitration catalyst matrix and an active component, wherein the active component is supported on the denitration catalyst matrix, characterized in that, The denitrification catalyst matrix is ​​the denitrification catalyst matrix according to any one of claims 1-7.

Citation Information

Patent Citations

  • Corrugated-plate type SCR (selective catalytic reduction) denitration catalyst

    CN102500424A

  • A preparation process for a corrugated plate denitrification catalyst

    CN106732709B

  • A substrate suitable for use in corrugated denitration catalysts and its molding and preparation method

    CN108404998B